The early warning efficiency analysis of secondary accidents in expressway tunnels. (March 2019) - Zhang, Bing; Xu, Weishuo; Liu, Guangtao; Muhammad, Ammar
Secondary accidents usually occur after an accident in a freeway tunnel. To this end, this article proposes an integrated safety early warning system for preventing secondary accidents in tunnels. First, we analyzed key parameters such as the average speed in the tunnel, the interior light sensitivity, and the driver's physiology, and proposed a safety warning model for tunnels. According to the driving rules of tunnels, an efficiency grooming model is proposed to analyze the delay of the traffic in tunnels and determine the best warning. Finally, the Jiulingshan Tunnel was simulated and verified by VISSIM software to analyze the feasibility and effectiveness of the model.